2004
DOI: 10.1007/s00449-004-0386-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dissolved oxygen and shear conditions on clavulanic acid production by Streptomyces clavuligerus

Abstract: Clavulanic acid (CA), a potent beta-lactamase inhibitor, is produced by a filamentous bacterium. Here, the effect of DO and shear, expressed as impeller tip velocity, on CA production was examined. Cultivations were performed in a 4 L fermentor with speeds of 600, 800 and 1,000 rpm and a fixed air flow rate (0.5 vvm). Also, cultivation with automatic control of dissolved oxygen, at 50% air saturation, by varying stirrer speed and using a mixture of air and O(2) (10% v/v) in the inlet gas, and a cultivation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 19 publications
3
55
1
5
Order By: Relevance
“…The dissolved oxygen concentration remained between 54 and 75% of the saturation with air, showing that there was no oxygen limitation. The negative effect of low DO concentration on CephC and CA production has been recognized previously (Rollins et al, 1988a;Rosa et al, 2005;Yegneswaran et al, 1991). However, in the present work the production of CephC and CA was not affected, since high DO levels were always present.…”
Section: Fed-batch Cultures With Starch Feedingcontrasting
confidence: 50%
See 1 more Smart Citation
“…The dissolved oxygen concentration remained between 54 and 75% of the saturation with air, showing that there was no oxygen limitation. The negative effect of low DO concentration on CephC and CA production has been recognized previously (Rollins et al, 1988a;Rosa et al, 2005;Yegneswaran et al, 1991). However, in the present work the production of CephC and CA was not affected, since high DO levels were always present.…”
Section: Fed-batch Cultures With Starch Feedingcontrasting
confidence: 50%
“…Previous work has shown that a high oxygen level is fundamental for the biosynthesis of CA and CephC (Rollins et al, 1988a(Rollins et al, , 1988b(Rollins et al, , 1991Rosa et al, 2005;Yegneswaran et al, 1988Yegneswaran et al, , 1991. The influence of carbon source and feeding conditions on production of both CA and CephC should therefore be studied under conditions that are not oxygen limited, which is possible using submerged bioreactor cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The strain did not reduce nitrate to nitrite, and it hydrolyzed the starch ( Table 2). With auxiliary identification, some physiological appeals, such as degradation of starch, gelatin, and decline of nitrate, are also well-thought-out to determine the species' taxonomy of novel isolates strains as commended by Rosselló-Mora and Amann [40].…”
Section: Physiological and Biochemical Propertiesmentioning
confidence: 99%
“…As Tabelas 1 e 2 apresentam a composição do meio de reativação, crescimento e produção, respectivamente (ROSA et al, 2005;TEODORO et al, 2006 …”
Section: Meio De Culturaunclassified